Capital Flows in Central and Eastern Europe : Evidence and Policy Options - Vegh Gramont, Carlos (IMF Working Papers; Working Paper ;, 1995)
This paper examines the nature and composition of capital flows in selected countries in Central and Eastern Europe during 1987-93. The data show that there was a remarkable turnaround in the capital account in 1992-93. This improvement was accompanied by widening current account deficits, an increase in real consumption, and real exchange rate appreciation. In light of these developments, the paper discusses the main macroeconomic concerns raised by capital inflows and lays out the principal policy options relevant for the transition economies.